High Individual Heterogeneity of Neutralizing Activities against the Original Strain and Nine Different Variants of SARS-CoV-2 - Rita Jaafar (MDPI AG, 2021)
Background: Since the beginning of the COVID-19 pandemic, several SARS-CoV-2 variants have sequentially emerged. In France, most cases were due to spike D641G-harbouring viruses that descended initially from the Wuhan strain, then by the variant of B.1.160 lineage we called Marseille-4 since the summer of 2020, which was followed by the Alpha and Beta variants in early 2021, then the Delta variant currently. Methods: We determined the neutralising antibody (nAb) titres in sera from convalescent individuals previously infected by these four major local variants and from vaccine recipients to the original Wuhan strain and nine variants, including two recent circulating Delta isolates. Results: The results show high inter-individual heterogeneity in nAbs, especially according to the variant tested. The major variations among nAbs are based on the genotype responsible for the infection. Patients previously infected with the beta and B.1.160 variants had the lowest nAb titres. We show that this heterogeneity is well explained by spike protein mutants modelling using in silico approaches. The highest titres were observed in individuals vaccinated with the Pfizer/BioNTech COVID-19 vaccine, even against the delta variant. Conclusions: Immunity acquired naturally after infection is highly dependent on the infecting variant, and, unexpectedly, mRNA-based vaccine efficacy was shown to be often better than natural immunity in eliciting neutralising antibodies.